2022
DOI: 10.18699/vjgb-22-59
|View full text |Cite
|
Sign up to set email alerts
|

Virulence potential of faecal <i>Escherichia coli</i> strains isolated from healthy cows and calves on farms in Perm Krai

Abstract: Cattle are a reservoir of pathogenic and potentially pathogenic Escherichia coli (E. coli) strains, which can pose a threat to human and animal health. The aim of the study was to evaluate the occurrence of 22 virulence-associated genes (VAGs), as well as the prevalence of antimicrobial drug resistance and three different bla-genes among 49 E. coli strains isolated from healthy cattle. The presence of VAGs that are common among diarrheagenic E. coli (DEC) strains and/or extraintestinal pathogenic E. coli (ExPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“… Khalifeh and Obaidat (2022) observed that 97 and 32% of the bovine strains carried fimH and papC , respectively, and these strains typically carried two or more virulence genes. Additionally, Mihailovskaya et al (2022) reported that fimH (91.8%), afa (61.2%), iutA (44.9%), and papC (20.4%) were predominant in the virulence genes carried by ExPEC. In this study, we observed that the main virulence genes carried by E. coli were ompF (100%), traT (100%), fimH (97%), and papC (96%), and each strain contained multiple virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“… Khalifeh and Obaidat (2022) observed that 97 and 32% of the bovine strains carried fimH and papC , respectively, and these strains typically carried two or more virulence genes. Additionally, Mihailovskaya et al (2022) reported that fimH (91.8%), afa (61.2%), iutA (44.9%), and papC (20.4%) were predominant in the virulence genes carried by ExPEC. In this study, we observed that the main virulence genes carried by E. coli were ompF (100%), traT (100%), fimH (97%), and papC (96%), and each strain contained multiple virulence genes.…”
Section: Discussionmentioning
confidence: 99%